Design and Economic Evaluation of Electrification of Small Villages in Rural Area in Yemen Using Stand-Alone PV System - Al-Shetwi, Ali Q.; Muhamad Zahim, Sujod; Al Tarabsheh, A.; Altawil, Ibrahim A. (ijrer.org, 2016)
The photovoltaic (PV) technology potential for Yemen is relatively high, based on this fact, there are many isolated and remote locations are located far away from the electrical national grid and cannot be linked in the near future. Hence, the electrification of these rural areas using PV system is very suitable solution to solve the problem of lighting and access to the development of these villages. This paper presents a study on the design and cost estimation of stand-alone photovoltaic PV system (SAPS) to supply the required electricity for these villages. The sizing of the suggested SAPS is achieved, such that radiation data, the electrical load for the typical household in the target villages are taken into account during the sizing steps. Furthermore, there are a maximum power point tracking (MPPT), an inverter, charge controller and lead acid battery which used as an energy storage system were designed. The MATLAB/Simulink used to simulate the PV array sizing and its characteristics depending on incremental conductance MPPT technique to enhance the efficiency of the modules and get maximum available power. The simulation result have been matched the sizing calculation result. Finally, the life cycle cost (LCC) analysis used to evaluate the economic feasibility of the system. The economical results proved that, there is a difference between the conventional energy systems and PV system in that they have a low operating cost and high initial cost. As a result, this study encouraged the using of PV systems to electrify the remote villages in Yemen.